Micro-CT analysis of the marginal adaptation and porosity associated with ultrasonic activation of coronally placed tricalcium silicate-based cements - DİNÇER, Asiye Nur; DİNÇER, ASİYE NUR; GÜNEŞER, MEHMET BURAK; GÜNEŞER, MEHMET BURAK; Sisli, Selen Nihal (My University, 2020)
This study aimed to evaluate the effect of ultrasonic activation on coronal marginal adaptation and microporosity of tricalcium silicate-based materials. Sixty freshly extracted human maxillary lateral incisor teeth were instrumented with ProTaper Next X2 files followed by Peeso-Reamer burs, sizes 1 to 5. The specimens were randomly divided into six groups (n = 10): Group 1, Biodentine + hand condensation; Group 2, Biodentine + ultrasonic activation; Group 3, NeoMTA Plus + hand condensation; Group 4, NeoMTA Plus + ultrasonic activation; Group 5, ProRoot WMTA + hand condensation; and Group 6, ProRoot WMTA + ultrasonic activation. All tested materials were mixed mechanically and placed 2 mm underneath the cement-enamel junction by hand condensation or indirect ultrasonic activation. Volumetric analysis of the voids between the dentine wall and coronal barrier material and the porosity within the material was evaluated with micro-CT. There was no significant difference in marginal adaptation among the six groups (P > 0.05). Ultrasonic activation favoured a reduced microporosity in Biodentine Group (P < 0.001).